Xenograft materials in maxillary sinus floor elevation surgery: a systematic review with network meta-analyses. Issue 7 (September 2021) - Canellas, J.V.D.S.; Drugos, L.; Ritto, F.G.; Fischer, R.G.; Medeiros, P.J.D.
Abstract: A systematic review and network meta-analysis was conducted to compare different commercially available xenograft materials used in maxillary sinus floor elevation surgery (MSFES). Embase, PubMed, the Cochrane Library, Web of Science, Scopus, LILACS, and grey literature were searched up to 13 July 2020. Only randomised controlled trials (RCTs) were included. A frequentist network meta-analysis using a random effects model compared different commercially available xenograft materials. The primary outcomes were the percentage of newly-formed bone and residual bone-substitute rate. Both were measured by histomorphometric analysis from bone biopsies obtained during preparation of the implant site. Of the 659 studies initially identified, 11 involving 242 MSFES were included in the quantitative analyses. A total of six bone-substitute materials were analysed (Bio-Oss® (Geistlich Pharma), InduCera® Dual Coat, Lumina-Bone Porous® (Critéria), Osseous® (SIN - Sistema de Implantes Nacional), THE Graft® (Purgo Biologics), and Osteoplant Osteoxenon® (Bioteck)). The P-score estimation showed that Osteoplant Osteoxenon® produced the most newly-formed bone and reabsorbed faster than other xenograft materials after six months. The combination of Bio-Oss® plus bone marrow aspirate concentrate (BMAC) significantly increased the percentage of newly-formed bone compared with Bio-Oss® alone. In contrast, the addition of Emdogain® (Straumann) and leucocyte and platelet-rich fibrin (L-PRF) to Bio-Oss® did not significantly improve the amount of regenerated bone. Study-level data indicated that the percentage of newly-formed bone differs among commercially available xenograft materials. Osteoplant Osteoxenon® seems to result in the highest amount of new bone in MSFES.